06 Epoxyeicosatrienoic acid mediated cardioprotection involves mitochondrial caveolin-1 and PKCe. Issue 24 (24th November 2011) - Chaudhary, K R; Cho, W Jung; Daniel, E E; Seubert, J M
Abstract : Cytochrome P450 epoxygenases can metabolise arachidonic acid to epoxyeicosatrienoic acids (EETs) which have known cardioprotective effects. Subsequent metabolism of EETs by soluble epoxide hydrolase (sEH) reduces the protective effect. Caveolins (Cav-1, -2, and -3) are structural proteins that insert into the plasma membrane to form caveolae, which bind molecules important in cardiac signal transduction and function. The objective of this study was to assess the role of caveolins and PKCε in EET mediated cardioprotection. Hearts from sEH null (KO) and littermate control (WT) mice were perfused in Langendorff mode and subjected to 20 min ischaemia followed by 40 min reperfusion. Immunohistochemistry, immunoblot and electron microscopy were performed to study expression and ultrastructure. H9c2 cells were treated with 11, 12-EET (1 μM) for 10, 20, 60 and 120 min followed by subcellular fractionation and immunobloting. In WT heart, cav-1 and cav-3 were present in cardiomyocytes and endothelial cells at baseline. Following ischaemia, cav-1 but not cav-3 disappeared; moreover, caveolae were absent in WT hearts. Mitochondria and T-tubules were swollen and cristae of mitochondria were damaged. Improved post-ischaemic functional recovery observed in KO or WT hearts treated with 11, 12-EET corresponded with higher cav-1 expression in plasma membrane and mitochondrial fractions. Increased phosphoPKCε expression was observed in mitochondrial fractions of 11, 12-EET treated hearts. H9c2 cells treated with 11, 12-EETs showed a time-dependent increased in cav-1 and phosphoPKCε expression in mitochondrial fractions. Taken together, our data suggest EET-mediated cardioprotection results in increased mitochondrial expression of cav-1 and phosphoPKCɛ.